Initial and supplementary indication approval of new targeted cancer drugs by the FDA, EMA, Health Canada, and TGA: phase III studies - Michaeli, Daniel; Mills, Mackenzie; Michaeli, Christoph T.; Miracolo, Aurelio; Kanavos, Panos (Investigational new drugs, 2022)
Background. Previous research focused on the clinical evidence supporting new cancer drugs’ initial US Food and Drug Administration (FDA) approval. However, targeted drugs are increasingly approved for supplementary indications of unknown evidence and benefit. Objectives. To examine the clinical trial evidence supporting new targeted cancer drugs’ initial and supplementary indication approval in the US, EU, Canada, and Australia. Data and Methods. 25 cancer drugs across 100 indications were identified with FDA approval between 2009-2019. Data on regulatory approval and clinical trials were extracted from the FDA, European Medicines Agency (EMA), Health Canada (HC), Australian Therapeutic Goods Administration (TGA), and clinicaltrials.gov. Regional variations were compared with χ2-tests. Multivariate logistic regressions compared characteristics of initial and supplementary indication approvals, reporting adjusted odds ratios (AOR) with 95% confidence intervals (CI). Results. Out of 100 considered cancer indications, the FDA approved 96, the EMA 92, HC 86, and the TGA 83 (83%, p < 0.05). The FDA more frequently granted priority review, conditional approval, and orphan designations than other agencies. Initial approvals were more likely to receive conditional / accelerated approval (AOR: 2.69, 95%CI [1.07-6.77], p < 0.05), an orphan designation (AOR: 3.32, 95%CI [1.38-8.00], p < 0.01), be under priority review (AOR: 2.60, 95%CI [1.17-5.78], p < 0.05), and be monotherapies (AOR: 5.91, 95%CI [1.14-30.65], p < 0.05) than supplementary indications. Initial indications’ pivotal trials tended to be shorter (AOR per month: 0.96, 95%CI [0.93-0.99], p < 0.05), of lower phase design (AOR per clinical phase: 0.28, 95%CI [0.09-0.85], p < 0.05), and enroll more patients (AOR per 100 patients: 1.19, 95%CI [1.01-1.39], p < 0.05). Conclusions. Targeted cancer drugs are increasingly approved for multiple indications of varying clinical benefit. Drugs are first approved as monotherapies in rare diseases with a high unmet need. Whilst expedited regulatory review incentivizes this prioritization, indication-specific safety, efficacy, and pricing policies are necessary to reflect each indication’s differential clinical and economic value.